Penggunaan Dan Fungsi Gamat Di Daerah Aia Manih Kota Padang Di Sanggar Gamat Kutril - Jessya Harefa Fortuna; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2020)
Aia Manih region is one of the heirs of Gamat which is very existent in preservation. However, in recent years, Gamat is rarely used as an entertainment art for the local community. Thus, the purpose of this research is to find out the use and function of Gamatin the Aia Manih community, Padang City, in the Gamat Kutril Studio. There are several theories used in this study: the existence theory, usage theory, and function theory. This research is a qualitative research in the form of descriptive method. It gives clear explanation about the object studied. The research instrument was the researcher itself and was assisted by cameras, stationery, and interview lists. The data were analyzed through classifying primary data and secondary data then arranging them systematically. The results of this study show that there are several uses and functions of Gamat art in the AiaManih community. It is used at parties, welcoming events, inaugurations, and family gathering. There are also several functions. They functions are emotional expression, aesthetic pleasure, entertainment, communication, and physical reaction.